Educational mismatches and job resolution in South Korea, the USA, and Germany. (6th September 2018) - Jeong, Yeasung; Lee, Ayoung; Cho, Joonmo
Abstract : We examine the persistence of educational mismatches in relation to job mobility in South Korea, the USA, and Germany using ten‐year panel data. The USA, with a flexible labour market, has the highest job mobility, so mismatches for workers' jobs in terms of educational attainment are resolved via job mobility. In contrast, in Korea, which has a dual‐structure labour market where workers have limited job mobility between core and periphery sectors, the likelihood of being mismatched increases. In Germany, the educational system, which emphasises job training, makes it possible to resolve or extinguish mismatches via job mobility only for the youth; while job mobility does not help resolve mismatches in any other age groups. These findings indicate that the different patterns in job mobility resolving mismatches over the three countries may not only stem from the efficacy of job information systems or from reducing friction in the labour market but may also be an interactive outcome of various labour market institutions affecting flexibility, such as stratification or job competency.